Crisis, voice, reputation: organisational communication and university response to sexual violence cases - Setianingrum, Vinda Maya; Pramana (Faculty of Communications Science, Dr. Soetomo University, 2026)
This study examined how organisational communication constitutes crisis response, voice, and legitimacy in university sexual violence cases in Indonesia, a socio-political context shaped by strong cultural hierarchies, legal–bureaucratic governance and an ongoing transition from a culture of silence towards digitally mediated transparency. Drawing on a qualitative multiple-case study of Universitas Indonesia (UI), Universitas Riau (UNRI), and Universitas Andalas (UNAND), the study integrates the Communicative Constitution of Organisations (CCO) perspective with Rhetorical Arena Theory (RAT) to move beyond what universities formally stated towards how organisational reality, authority, and moral legitimacy were communicatively produced during crises. The findings indicate distinct communicative patterns across cases. Dialogic engagement was associated with the preservation of legitimacy, reactive communication facilitated short-term reputational repair, whereas bureaucratic shielding—manifested through reliance on procedural language, regulatory formalism, and strategic silence—intensified public scrutiny and moral contestation. Within the Indonesian digital public sphere, viral social media discourse functioned as a secondary constitutional force, capable of overriding formal organisational texts and compelling institutional responses. More importantly, the study demonstrates that control-oriented crisis communication strategies frequently backfired, as attempts to manage or conceal crisis narratives amplified counter-narratives and weakened institutional moral authority. This reinforces the long-standing insight that the cover-up may be more damaging than the crisis itself. The study contributes to organisational and crisis communication scholarship by challenging assumptions of centralised control and reputational management. It shows that, in morally charged crises such as sexual violence, legitimacy in Indonesian universities is grounded less in image maintenance and more in moral authority enacted through communicative openness, accountability, and dialogic engagement.